Advances in cerebral amyloid angiopathy imaging. (May 2019) - Chen, Szu-Ju; Tsai, Hsin-Hsi; Tsai, Li-Kai; Tang, Sung-Chun; Lee, Bo-Chin; Liu, Hon-Man; Yen, Ruoh-Fang; Jeng, Jiann-Shing
Cerebral amyloid angiopathy (CAA) is a cerebral small vessel disease caused by β -amyloid (Aβ) deposition at the leptomeningeal vessel walls. It is a common cause of spontaneous intracerebral hemorrhage and a frequent comorbidity in Alzheimer's disease. The high recurrent hemorrhage rate in CAA makes it very important to recognize this disease to avoid potential harmful medication. Imaging studies play an important role in diagnosis and research of CAA. Conventional computed tomography and magnetic resonance imaging (MRI) methods reveal anatomical alterations, and remains as the most reliable tool in identifying CAA according to modified Boston criteria. The vascular injuries of CAA result in both hemorrhagic and ischemic manifestations and related structural changes on MRI, including cerebral microbleeds, cortical superficial siderosis, white matter hyperintensity, MRI-visible perivascular spaces, and cortical microinfarcts. As imaging techniques advance, not only does the resolution of conventional imaging improve, but novel skills in functional and molecular imaging studies also enable in vivo analysis of vessel physiological changes and underlying pathology. These modern tools help in early detection of CAA and may potentially serve as sensitive outcome markers in future clinical trials. In this article, we reviewed past studies of CAA focusing on utilization of various conventional and novel imaging techniques in both research and clinical aspects.